Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

find the real solution(s), if any, of the system by examining the graph

Find The Real Solutions If Any Of The System By Examining The Graph class=

Sagot :

Given:

[tex]\begin{gathered} -6x-3y=18\ldots\ldots\ldots(1) \\ \frac{x^{2}}{9}+\frac{y^{2}}{36}=1\ldots\ldots\ldots\ldots(2) \end{gathered}[/tex]

Let us consider the equation (1),

[tex]\begin{gathered} -6x-3y=18 \\ -2x-y=6 \\ -y=2x+6 \\ y=-(2x+6)\ldots\ldots\ldots(3) \end{gathered}[/tex]

Substitute equation (3) in (2), we get

[tex]\begin{gathered} \frac{x^2}{9}+\frac{(-(2x+6))^2_{}}{36}=1 \\ \frac{4x^2}{36}+\frac{4x^2+36+24x}{36}=1 \\ \frac{4x^2+4x^2+36+24x}{36}=1 \\ 8x^2+36+24x=36 \\ 8x^2+24x=0 \\ 8x(x+3)=0 \\ x=0,x=-3 \end{gathered}[/tex]

Substitute x=0 and x=-3 in equation (3) we get,

[tex]\begin{gathered} y=-(2(0)+6) \\ =-6 \\ y=-(2(-3)+6) \\ =0 \end{gathered}[/tex]

Hence, the solutions are, (0,-6) and (-3,0).

Let us verify this, by substituting (0,-6) and (-3,0) in equation (1), we get

For (0, -6),

[tex]\begin{gathered} -6(0)-3(-6)=18 \\ 18=18 \end{gathered}[/tex]

For (-3, 0)

[tex]\begin{gathered} -6(-3)-3(0)=18 \\ 18=18 \end{gathered}[/tex]

Hence, it is verified.